Penerapan Digital Accounting pada Era Digitalisasi untuk Meningkatkan Performa UMKM di Kelurahan Nginden Jangkungan Surabaya - Devira Larasati; Ari Rohmana; Reza Mutiara; Maria Yovita R. Pandin (Journal of Management and Social Sciences, 2023)
Research using this qualitative method has the aim of knowing the application of digitization of accounting in MSME bookkeeping in the Nginden Jangkungan Village, Surabaya, and increasing understanding of the importance of digitalization in MSMEs. The population used in this study were MSMEs in the Nginden Jangkungan Village, Surabaya, and the samples were taken using a random sampling technique. The results of this study indicate that there are still several MSMEs that have not implemented a digital accounting system due to the lack of information they obtain to implement the system. However, several MSMEs have successfully implemented this digital accounting system. The existence of application of digital accounting can improve the performance of MSMEs in the Nginden Jangkungan Village area, Surabaya. The use of this digital accounting system can simplify the process of recording and reporting finances, avoiding the risk of data loss.